Applying plant-pollinator network to identify priority species for conservation in a biodiversity hotspot - Monteiro, Beatriz Lopes [UNESP]; Souza, Camila Silveira; Maruyama, Pietro K.; Camargo, Maria Gabriela Gutierrez [UNESP]; Morellato, Leonor Patricia Cerdeira [UNESP] (Elsevier, 2025)
Biotic pollination is a key ecosystem function, as 85 % of all Angiosperms depend on interactions with animals for reproduction. Anthropogenic impacts have caused a decrease in biodiversity, affecting species interactions and their conservation. Initiatives to evaluate species' conservation value usually do not consider the species interactions organized in a nonrandom pattern. Here we used network approaches to evaluate the role of endemic and/or threatened species in plant-pollinator interactions from a highly diverse and endangered tropical mountain grassland ecosystem, the campo rupestre. We asked how the mutualistic interactions are organized, which are the main species structuring the network, and whether endemic and/or threatened species are among the main species structuring the mutualistic interactions. The plant-pollinator network had 481 species performing 1264 interactions. Twenty species are under threat and 42 are endemic. Through the categorization of species according to modularity roles and core-periphery status in the network, we created a conservation priority list with nine plant and pollinator species. Endemic plants, the native bumblebee Bombus pauloensis, and small and short-tongued bees, as well as hummingbirds, were identified as crucial for network cohesiveness. The introduced honeybee Apis mellifera emerged as an important species through network analysis, and its role in the community dynamic deserves further investigation. Our study illustrates the usefulness of network approaches in combination with ancillary data, such as species threat status and endemism, to guide conservation efforts in highly biodiverse and threatened tropical ecosystems.